2020
DOI: 10.7554/elife.59994
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a molecular glue promoting CDK12-DDB1 interaction to trigger cyclin K degradation

Abstract: Molecular-glue degraders mediate interactions between target proteins and components of the ubiquitin-proteasome system to cause selective protein degradation. Here, we report a new molecular glue HQ461 discovered by high-throughput screening. Using loss-of-function and gain-of-function genetic screening in human cancer cells followed by biochemical reconstitution, we show that HQ461 acts by promoting an interaction between CDK12 and DDB1-CUL4-RBX1 E3 ubiquitin ligase, leading to polyubiquitination and degrada… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 49 publications
2
130
0
Order By: Relevance
“…Rather they showed that CDK12, which normally does not act as a E3 substrate receptor, binds DDB1 in the presence of CR-8, positioning cyclin K into the ubiquitination zone (radius from E3 ligase where accessible lysine residues on substrate can be marked with ubiquitin). Interestingly, similar results have now been published by the Winter ( 149 ) and Wang ( 150 ) groups. These studies show that other parts of the E3 ligase complex than the substrate recognition subunit may be amenable to hijacking for TPD.…”
Section: Hijacking the Ups: Molecular Gluessupporting
confidence: 85%
“…Rather they showed that CDK12, which normally does not act as a E3 substrate receptor, binds DDB1 in the presence of CR-8, positioning cyclin K into the ubiquitination zone (radius from E3 ligase where accessible lysine residues on substrate can be marked with ubiquitin). Interestingly, similar results have now been published by the Winter ( 149 ) and Wang ( 150 ) groups. These studies show that other parts of the E3 ligase complex than the substrate recognition subunit may be amenable to hijacking for TPD.…”
Section: Hijacking the Ups: Molecular Gluessupporting
confidence: 85%
“…Molecular glues can also elicit transcription factor degradation by means other than directly attracting an E3 ligase: Compounds that bind BCL6, for example, trigger formation of BCL6 fibers that recruit the E3 ligase SIAH1 and counteract BCL6‐dependent gene repression in lymphoma cells (Kerres et al, 2017; Slabicki et al, 2020b). Moreover, molecular glues can affect the activity of RNA Pol II itself, by controlling the stability of a cyclin‐dependent kinase that regulates transcript elongation (Mayor‐Ruiz et al, 2020; Lv et al, 2020; Slabicki et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Oncology: Her2+ and triple-negative breast tumors [111] Covalent protac BTK and BLK CRBN Oncology: chronic lymphocytic leukemia [112] Covalent protac Platform for Halo-tagged proteins. VHL Research use [115] Covalent protac Platform for GFP-tagged proteins VHL Research use [117] Click protac BRD4 and ERK1/2 CRBN Oncology [119] Molecular glue RBM39 E3 ligase receptor DCAF15 Oncology [122] Molecular glue RBM39, cyclinK CRBN Oncology [123] Molecular glue DDB1-CDK12 molecular glue CRBN Oncology [124] Molecular glue CDK12-cyclin K CRBN Oncology [125] Allosteric modulator Aspartate decarboxylase PanD E3-independent Research use, anti-microbial agents [131] Ubiquitin-independent degrader Androgen receptor (AR) (F876L) ND (indirectly, CHIP) Oncology: prostate cancer [137] Ubiquitin-independent degrader Her3 (ErbB3)…”
Section: Concluding Remarks: An Exciting Third Generation Of Protein-mentioning
confidence: 99%
“…The fact that the discovery of molecular glues has been so far the result of serendipity has prompted researchers to define rational methods to discover novel molecules acting as glues [ 123 ]. Two recent papers have used distinct approaches, bioinformatics and molecular screening, to establish new molecular glue candidates, somehow converging in identifying and characterizing outstanding cyclin K degraders [ 124 , 125 ] ( Figure 2 ). The Ebert lab bioinformatically analyzed the data of more than 4500 drugs tested against close to 600 cancer cell lines with mRNA levels of 500 E3 ligases, determining more than 67,000 correlations, and established a link between the Cul4 adaptor protein DDB1’s expression levels and the CDK inhibitor CR8’s [ 126 ] sensitivity.…”
Section: Modulating the Reactivity And Versatility Of Proteolytic mentioning
confidence: 99%
See 1 more Smart Citation